2007
DOI: 10.1002/anie.200604253
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and Intracellular Production of Peptide‐Encapsulated Fluorescent Silver Nanoclusters

Abstract: Every nucleolus has a silver lining: Formation of silver nanoclusters by fluorescence photoactivation was used for the staining of cells at low silver nitrate concentrations and ambient temperature. The picture shows picosecond lifetime images of peptide‐encapsulated silver nanoclusters within NIH 3T3 cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
220
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 303 publications
(224 citation statements)
references
References 18 publications
1
220
1
2
Order By: Relevance
“…Some biomacromolecules, such as cell-penetrating peptides (CPPs), may be capable of penetrating membranes without overt lipid bilayer disruption/poration [12][13][14][15] . Likewise, synthetic nanomaterials with very small dimensions (molecules, metal nanoclusters 16 , small dendrimers 10 and carbon nanotubes 17 ) can also pass through cell membranes. However, to the best of our knowledge, no synthetic material larger than a few nanometres in size can pass through membranes without disrupting the integrity of these biological barriers.…”
mentioning
confidence: 99%
“…Some biomacromolecules, such as cell-penetrating peptides (CPPs), may be capable of penetrating membranes without overt lipid bilayer disruption/poration [12][13][14][15] . Likewise, synthetic nanomaterials with very small dimensions (molecules, metal nanoclusters 16 , small dendrimers 10 and carbon nanotubes 17 ) can also pass through cell membranes. However, to the best of our knowledge, no synthetic material larger than a few nanometres in size can pass through membranes without disrupting the integrity of these biological barriers.…”
mentioning
confidence: 99%
“…[1][2][3][4] Owing to the strong quantum size confinement in this size range (o 2 nm), NCs possess discrete and size-tunable electronic transitions and display unique molecule-like properties, such as quantized charging and luminescence. [5][6][7][8][9][10][11][12] Strong luminescence is one of the most attractive features of these NCs owing to their ultrafine size, good photostability and low toxicity; 13 some of these properties may not be realized by other luminophores, such as organic dyes (for example, photostability concerns) and semiconductor quantum dots (for example, relatively large size and toxicity concerns). 2,8,9,14,15 Recent studies have shown that luminescent Au and Ag NCs are promising optical probes for bioimaging and biosensing applications.…”
Section: Introductionmentioning
confidence: 99%
“…In general, passage across the lipid bilayer follows active or passive transport [15]. Active uptake processes follow energy-dependent endocytotic or pinocytotic pathways, while passive transport is energy-independent and characteristically reserved for small molecules/particles that diffuse through small protein channels or the lipid bilayer itself [16]. Most delivery vectors are trapped inside endosomal compartments, leading to a weak pharmacokinetic profile [17][18][19].…”
Section: Introductionmentioning
confidence: 99%